Studi Literatur Pengendalian Koksidiosis pada Ternak Ruminansia di Lahan Kering Nusa Tenggara Timur - Anjelika Masneno; Aji Winarso; Yohanes TRMR Simarmata (Jurnal Veteriner Nusantara, 2023)
Coccidiosis is a gastrointestinal parasitic disease caused by the protozoan Eimeria spp. The infective form of Eimeria is the oocyst that can be found in almost all tropical environmental conditions and the possibility of disease as an opener to other agents. The percentage of coccidiosis incidence in East Nusa Tenggara (NTT) is increasing from year to year, this is due to many factors that play a role in the spread of coccidiosis in livestock. One of them is the level of resistance of Eimeria oocysts, which can last a long time, so that they remain vigilant and more attention needs to be paid to prevent the spread. The purpose of compiling this literature study is to determine the risk factors associated with the incidence of coccidiosis in ruminants and control of coccidiosis in ruminants in dry land of East Nusa Tenggara. This literature study was obtained from searching and collecting from various reference sources using Google Scholar with the help of the Mendeley application. There are 53 literatures obtained and after being analyzed and known risk factors related to the incidence of coccidiosis are maintenance management, season (temperature and humidity), environmental conditions, age of livestock, and sex. Coccidiosis control in ruminants can be done with coccidiostat therapy and herbal ingredients as well as improving management this case regular sanitation and cleanliness of cages, stables for adults and young livestock, rotation of pastures, containers or feed containers on a regular basis and endeavored to avoid contamination by feces.